PID控制器表达式为:
[u(t) = K_pe(t) + K_iint_0^t e( au)d au + K_dfrac{de(t)}{dt}
]
离散化:
令 $ t = nT,~T$为采样周期。可得:
[e(t) = e(nT) \\
int_0^t e( au)d au = sum_{i=0}^{n-1} e(iT) \\
frac{de(t)}{dt} = frac{e(nT)-e[(n-1)T]}{T}
]
因为(T)是固定的,不妨设为1,可简化为:
[e(t) = e(n) \\
int_0^t e( au)d au = sum_{i=0}^n e(i) \\
frac{de(t)}{dt} = e(n)-e(n-1) ]
所以:
[u(n) = K_pe(n) + K_isum_{i=0}^n e(i) + K_d[e(n)-e(n-1)]
]
增量化:
令 (Delta u(n) = u(n) - u(n-1)) 可得:
[ egin{aligned}
Delta u(n) &=
{K_pe(n) + K_isum_{i=0}^n e(i) + K_d[e(n)-e(n-1)]} \\
&~~~~ - {K_pe(n-1) + K_isum_{i=0}^{n-1} e(i) + K_d[e(n-1)-e(n-2)]} \\
&= (K_p + K_i + K_d)e(n) - (K_p + 2K_d)e(n-1) + K_de(n-2)
end{aligned} ]
所以:
[ egin{aligned}
u(n) &= u(n-1) + Delta u(n) \\
Delta u(n) &= a_0e(n) + a_1e(n-1) + a_2e(n-2) \\
a_0 &= K_p + K_i + K_d \\
a_1 &= -(K_p + 2K_d) \\
a_2 &= K_d
end{aligned} ]
C语言实现
dpid.h:
#ifndef __DPID_H__
#define __DPID_H__
typedef struct
{
float Kp, Ki, Kd;
float a[3];
float e[3];
}dpid_t;
void dpid_init(dpid_t *pid, float Kp, float Ki, float Kd);
float dpid(dpid_t *pid, float e);
#endif
dpid.c:
#include "dpid.h"
void dpid_init(dpid_t *pid, float Kp, float Ki, float Kd)
{
pid->Kp = Kp;
pid->Ki = Ki;
pid->Kd = Kd;
pid->a[0] = Kp + Ki + Kd;
pid->a[1] = -(Kp + 2*Kd);
pid->a[2] = Kd;
pid->e[0] = pid->e[1] = pid->e[2] = 0;
}
float dpid(dpid_t *pid, float e)
{
//! 更新误差
pid->e[2] = pid->e[1];
pid->e[1] = pid->e[0];
pid->e[0] = e;
return pid->a[0]*pid->e[0]
+ pid->a[1]*pid->e[1]
+ pid->a[2]*pid->e[2];
}